Analysis of the Movement of Rice Field Rats (Rattus argentiventer) Using the Linear Trap Barrier System - Hamdan Maruli Siregar; Swastiko Priyambodo; Dadan Hindayana (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2021)
Linear Trap Barrier System (LTBS) is an innovative control technology developed using a trap system to control the movement of rice field rats. This study aims to determine the catch pattern and catch direction of rice field rats in several phases of rice plant growth. The experiment carried out was the installation of 6 LTBS units in 2 types of rice field rats habitat, i.e., village border and irrigation embankments. LTBS was installed in 3 phases of rice plant growth, i.e., vegetative, early generative, and late generative. The results showed that the installation of LTBS in both habitats had the same catch pattern, i.e., the highest percentage of rat catch occurred in the early generative phase. Likewise, the direction of rat catch in each phase of rice growth also showed the same pattern, i.e., the number of rats caught in the entry trap was relatively the same as the number of rats caught in the exit trap.